Lycopene supplementation restores vitamin A deficiency in mice and possesses thereby partial pro‐vitamin A activity transmitted via RAR signaling. Issue 11 (29th July 2016) - Aydemir, Gamze; Kasiri, Yasamin; Bartók, Emöke‐Márta; Birta, Eszter; Fröhlich, Kati; Böhm, Volker; Mihaly, Johanna; Rühl, Ralph
Abstract : It is explored, whether lycopene possesses pro‐vitamin A (VA) activity comparable to known VA derivatives. It is found that lycopene can restore VA deficiency and compensate VA for retinoic acid receptor (RAR)‐mediated signaling as the major function of VA in the mammalian organism. Lycopene administration can initiate upregulation of RAR‐mediated signaling in various organs in VA deficient diet fed animals via potential novel bioactive lycopene metabolites. This indicates that lycopene possesses partial pro‐VA activity in mice transmitted via RAR‐mediated signaling. Abstract : Scope: The aim of this study was to compare if lycopene also possesses pro‐vitamin A (VA) activity comparable to known VA derivatives. Materials and methods: We used a transgenic retinoic acid response element reporter mouse model ( n = 8, per group) for this study, and after the initial wash out of VA using a vitamin A deficient diet (VAD) for 18 weeks, the animals were supplemented further with (a) VAD‐fed mice, (b) VAD‐fed mice plus retinol (20 mg/kg bw), (c) VAD‐fed mice plus β‐carotene (40 mg/kg bw), and (d) VAD‐fed mice plus lycopene (40 mg/kg bw). Using ex vivo scanning and gene expression analysis of retinoid target and VA marker gene analysis in various organs of these supplemented mice (b, c, d), we found increased luciferase activity and normalized marker and target gene analysis compared to group a. Conclusions: Lycopene can restore VA deficiency and compensate VA for retinoic acid receptor (RAR)‐mediated signaling as the major function of VA in the mammalian organism. Lycopene administration can initiate upregulation of RAR‐mediated signaling in various organs in VAD‐fed animals via potential novel bioactive lycopene metabolites. This indicates that lycopene possesses partial pro‐VA activity in mice transmitted via RAR‐mediated signaling.